2018
DOI: 10.2118/190305-pa
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Dominated Proxy Model for Solvent Injection in Ultratight Oil Reservoirs

Abstract: Summary Enhanced oil recovery (EOR) by solvent injection offers significant potential to increase recovery from shale oil reservoirs, which is typically between 3 and 7% original oil in place (OOIP). The rather sparse literature on this topic typically models these tight reservoirs on the basis of conventional-reservoir processes and mechanisms, such as by convective transport using Darcy's law, even though there is little physical justification for this treatment. The literature also downplays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…If this bending pressure is extrapolated to a permeability close to zero, as depicted in Figure 19, the extrapolated pressure is the same as the first contact minimum miscibility pressure (FCMMP) of CO 2 and Bakken oil, which is 4940 psia from the swelling test calculations shown in Figure 20. These results are consistent with the conclusion of Cronin et al [25] who found that for diffusion-dominated systems, only FCMMP is important and MCMMP is not applicable in gas flooding of ultra-tight reservoirs. Similarly, for pressures lower than the MMP, the recovery of heterogeneous pore size reservoir is lower than 10 nm pore size homogenous reservoir but higher than 10 µm pore size homogenous case.…”
Section: Slim Tube Simulations and Mmpsupporting
confidence: 93%
“…If this bending pressure is extrapolated to a permeability close to zero, as depicted in Figure 19, the extrapolated pressure is the same as the first contact minimum miscibility pressure (FCMMP) of CO 2 and Bakken oil, which is 4940 psia from the swelling test calculations shown in Figure 20. These results are consistent with the conclusion of Cronin et al [25] who found that for diffusion-dominated systems, only FCMMP is important and MCMMP is not applicable in gas flooding of ultra-tight reservoirs. Similarly, for pressures lower than the MMP, the recovery of heterogeneous pore size reservoir is lower than 10 nm pore size homogenous reservoir but higher than 10 µm pore size homogenous case.…”
Section: Slim Tube Simulations and Mmpsupporting
confidence: 93%
“…Counter-diffusion occurs during the huff and soak because solvent diffuses from fractures into matrix while hydrocarbon simultaneously diffuses into the fractures 6,19,26 . However, in this study, we assume a constant pore volume and ignore mass transfer between V wf and ultratight matrix when using Eq.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…These correlations can provide insight into drilling locations and expected recoveries, but they are not fundamentally based on the underlying physics and require significant historical data. Instead, maximum recovery (at infinite time) can be easily quantified by the density reduction between initial and producing conditions, which is independent of fracture-matrix contact area and transport rates 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations